Prototype Alat Penyiram Otomatis Pada Bunga Berbasis Arduino Uno - asrul, Fadli Tamrin (Celebes Engineering Journal, 2021)
In the midst of the current Covid-19 pandemic, some people use their free time to grow crops at home, this farming activity certainly requires maintenance so that plants can grow well, one of which is by watering the plants every morning and in the afternoon. In general, people still water the plants manually. This study proposes automatic watering of plants based on Arduino UNO with the help of a sensor module timer/RTC (Real Time Clock) which functions as a timer/duration of this automatic watering prototype and determines when this prototype runs and stops. Also with the help of an aquarium pump that can work automatically with high-voltage electric current, assistance from a power source/charge adapter with a voltage of 9 V and a power of 2 A, with I/O as input and output of this prototype, a relay that functions as a switch with electromagnetic principles , and coil / coil. The water resources for this automatic watering prototype use PDAM/Water at home, the LED light on the prototype of this tool serves as an indicator/sign on the prototype automatic watering of this tool running commands from the Arduino UNO program. Protoype This tool also uses the LCD as a display display showing the time and alarm, as well as running text.